2022
DOI: 10.1111/apha.13772
|View full text |Cite
|
Sign up to set email alerts
|

Assessing mitochondrial respiration in permeabilized fibres and biomarkers for mitochondrial content in human skeletal muscle

Abstract: Aim: Assessments of mitochondrial respiration and mitochondrial content are common in skeletal muscle research and exercise science. However, many sources of technical and biological variation render these analyses susceptible to error. This study aimed to better quantify the reliability of different experimental designs and/or techniques so as to assist researchers to obtain more reliable data. Methods:We examined the repeatability of maximal mitochondrial oxidative phosphorylation in permeabilized muscle fib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…Furthermore, variability of CS activity in different samples obtained from the same muscle biopsy might also be a contributory factor. The variability of resting high‐resolution respirometry data in this study is within that previously reported in the literature (Cardinale et al., 2018 ; Kuang et al., 2022 ); nevertheless, this remains an important consideration, and caution should be exercised when interpreting the results relating to CIL. Examination of the relative contributions of CIL to P and E, demonstrated in InvRCR and LCR, therefore provides a more appropriate representation of the potential for IPC to maintain mitochondrial coupling efficiency.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, variability of CS activity in different samples obtained from the same muscle biopsy might also be a contributory factor. The variability of resting high‐resolution respirometry data in this study is within that previously reported in the literature (Cardinale et al., 2018 ; Kuang et al., 2022 ); nevertheless, this remains an important consideration, and caution should be exercised when interpreting the results relating to CIL. Examination of the relative contributions of CIL to P and E, demonstrated in InvRCR and LCR, therefore provides a more appropriate representation of the potential for IPC to maintain mitochondrial coupling efficiency.…”
Section: Discussionsupporting
confidence: 83%
“…Correcting to CI+IIP as a marker of mitochondrial content might then be useful to adjust for baseline differences and to reduce the influence of variability in CS activity in different samples from the same muscle biopsy (Kuang et al, 2022). These data collectively corroborate the finding of greater CIL after exercise in SHAM, but not IPC, evidenced in the more established normalizations to wet mass and CS activity, again with no difference in the baselines (P = 0.36).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It has been suggested that the increases in fibre cross-sectional area (fCSA) observed following resistance training may dilute, and therefore mask, the magnitude of mitochondrial volumetric adaptations (MacDougall et al ., 1979; Lüthi et al ., 1986; Parry et al ., 2020). Therefore, given that the use of biochemical assays to interrogate mitochondrial adaptations (Larsen et al ., 2012; Kuang et al ., 2022) are unable to account for difference in fCSA, the use of transmission electron microscopy (TEM) may better reveal the distinct structural mitochondrial characteristics of resistance-trained individuals, such as mitochondrial morphology (Castro-Sepulveda et al ., 2020) and cristae density (Nielsen et al ., 2017b), that are independent of fCSA.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the increases in fibre cross‐sectional area (fCSA) observed following resistance training may dilute, and therefore mask, the magnitude of mitochondrial volumetric adaptations (Lüthi et al., 1986; MacDougall et al., 1979; Parry et al., 2020). Therefore, given that the use of biochemical assays to interrogate mitochondrial adaptations (Kuang et al., 2022; Larsen et al., 2012) are unable to account for difference in fCSA, the use of transmission electron microscopy (TEM) may better reveal the distinct structural mitochondrial characteristics of resistance‐trained individuals, such as mitochondrial morphology (Castro‐Sepulveda et al., 2020) and cristae density (Nielsen, Gejl et al., 2017), that are independent of fCSA.…”
Section: Introductionmentioning
confidence: 99%